miR-122 promotes hepatic lipogenesis via inhibiting the LKB1/AMPK pathway by targeting Sirt1 in non-alcoholic fatty liver disease - Long, Jun-Ke; Dai, Wen; Zheng, Ya-Wen; Zhao, Shui-Ping (Molecular medicine (Cambridge, Mass.), 2019)
Non-alcoholic fatty liver disease (NAFLD) is a common hepatic disease with an increasing prevalence but an unclear aetiology. This study aimed to investigate the functional implications of microRNA-122 (miR-122) in the pathogenesis of NAFLD and the possible molecular mechanisms. Both in vitro and in vivo models of NAFLD were generated by treating HepG2 and Huh-7 cells with free fatty acids (FFA) and by feeding mice a high-fat diet (HFD), respectively. HE and Oil Red O staining were used to examine liver tissue morphology and lipid deposition, respectively. Immunohistochemical (IHC) staining was used to examine Sirt1 expression in liver tissues. qRT-PCR and Western blotting were employed to measure the expression of miR-122, Sirt1, and proteins involved in lipogenesis and the AMPK pathway. Enzyme-linked immunosorbent assay (ELISA) was used to quantify triglyceride (TG) levels in HepG2 and Huh-7 cells and in liver tissues. The interaction between miR-122 and the Sirt1 gene was further examined by a dual luciferase reporter assay and RNA-immunoprecipitation (RIP). NAFLD hepatic tissues and FFA-treated HepG2 and Huh-7 cells presented excess lipid production and TG secretion, accompanied by miR-122 upregulation, Sirt1 downregulation, and potentiated lipogenesis-related genes. miR-122 suppressed Sirt1 expression via binding to its 3'-untranslated region (UTR). Knockdown of miR-122 effectively mitigated excessive lipid production and suppressed the expression of lipogenic genes in FFA-treated HepG2 and Huh-7 cells via upregulating Sirt1. Furthermore, miR-122 knockdown activated the LKB1/AMPK signalling pathway. The inhibition of miR-122 protects hepatocytes from lipid metabolic disorders such as NAFLD and suppresses lipogenesis via elevating Sirt1 and activating the AMPK pathway. These data support miR-122 as a promising biomarker and drug target for NAFLD.